Superparamagnetic magnesium ferrite nanoparticles fabricated by a simple, thermal-treatment method - Naseri, Mahmoud Goodarz; Majles Ara, Mohammad Hossein; Saion, Elias; Shaari, Abdul Halim (Elsevier, 2014)
This study investigated the synthesis of magnesium ferrite (MgFe2O4) nanoparticles with cubic symmetry that were prepared by a thermal-treatment method by using a solution that contained poly (vinyl alcohol) (PVA) as a capping agent and Mg and Fe nitrates as alternative sources of metal. Heat treatment was conducted using an electric cylinder furnace in an air atmosphere at temperatures between 673 and 973 K, and magnesium ferrite nanoparticles were produced that had different crystallite sizes ranging from5 to 8 nm. The products were well characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscope (FESEM), X-ray analysis (EDXA), and Fourier transform infrared spectroscopy (FT-IR). All the samples calcined from 673 to 973 K exhibited super paramagnetic behavior with unpaired electrons spins, which was confirmed by using a vibrating sample magnetometer (VSM) and electron paramagnetic resonance (EPR) spectroscopy.